The implications of self growth on child language - Ali Hassan, Elsayed Makki Elbishr; Suleiman, Hassan (Scientific Institute for Advanced Training and Studies, 2020)
This study focused on the effect of infant personal growth towards stages of language acquisition. It aims to discuss on personal growth stages and the objective of the study, and the extent of its effect in shaping the child’s language. It proposes a necessary question; does the study of personal growth stages can sufficiently rely on observation alone? Similarly, this research touches upon the importance of external factors that can affect the child’s life and language, and gives an idea on the development of foetus in its early weeks, and the relationship of the mother with the foetus, in terms of understanding the significance and educational relationship between the psychological and health condition of the mother and her foetus as a child-to-be, and how it passively and actively affects its psychology, stimulation, emotion and language in the future life. The current reality has shown that the early stage of infancy is crucial for the future life of a person as children in this stage of growth begin to properly adapt themselves with the external environment just as how cultures and traditions constitute their first lesson in life. No doubt that a child’s language acquisition is important in shaping a strong presence of his attempt to adapt to the very environment that he lives. This research concludes that personal growth has a major role in affecting the child’s language. The author suggests that it is necessary to materialize several applied linguistic and educational programmes and have them recognized to fruitfully benefit from the stages of growth in orientating the child’s education and language acquisition until he has obtain sound education based upon modern scientific foundations.